Mhc supertypes confer both qualitative and quantitative resistance to avian malaria infections in a wild bird population. - Sepil, I; Lachish, S; Hinks, A; Sheldon, B (2013)
Major histocompatibility complex (Mhc) genes are believed to play a key role in the genetic basis of disease control. Although numerous studies have sought links between Mhc and disease prevalence, many have ignored the ecological and epidemiological aspects of the host-parasite interaction. Consequently, interpreting associations between prevalence and Mhc has been difficult, whereas discriminating alleles for qualitative resistance, quantitative resistance and susceptibility remains challenging. Moreover, most studies to date have quantified associations between genotypes and disease status, overlooking the complex relationship between genotype and the properties of the Mhc molecule that interacts with parasites. Here, we address these problems and demonstrate avian malaria (Plasmodium) parasite species-specific associations with functional properties of Mhc molecules (Mhc supertypes) in a wild great tit (Parus major) population. We further show that correctly interpreting these associations depends crucially on understanding the spatial variation in risk of infection and the fitness effects of infection. We report that a single Mhc supertype confers qualitative resistance to Plasmodium relictum, whereas a different Mhc supertype confers quantitative resistance to Plasmodium circumflexum infections. Furthermore, we demonstrate common functional properties of Plasmodium-resistance alleles in passerine birds, suggesting this is a model system for parasite-Mhc associations in the wild.